Raising the Speed Limit US Economic Growth in the Information Age - Jorgenson, Dale Weldeau 1933-2022 (OECD Economics Department Working Papers, 2000)
This paper examines the underpinnings of the successful performance of the US economy in the late 1990s. Relative to the early 1990s, output growth has accelerated by nearly two percentage points. We attribute this to rapid capital accumulation, a surge in hours worked, and faster growth of total factor productivity. The acceleration of productivity growth, driven by information technology, is the most remarkable feature of the US growth resurgence. We consider the implications of these developments for the future growth of the US economy ...